Long Term Trends in Steel Consumption - Roland Döhrn; Karoline Krätschell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Since the iron and steel sector contributes considerably to industrial CO2 emissions it is important to identify the underlying factors driving steel demand. Using a panel dataset this paper examines the interrelation of steel demand with GDP and its composition, in particular the investment share since investment goods can be expected to be particularly steel intensive. Our analysis confirms that there seems to be an increase of steel demand in an initial stage of economic development and a decline after economies have reached a certain level of per capita income. Moreover, we fi nd some evidence that carbon leakage do not seem to play a role in the steel sector. – – Da Eisen- und Stahlindustrie stark zu industriellen CO2-Emissionen beitragen, ist es wichtig grundlegende Faktoren zu identifizieren, die die Stahlnachfrage treiben. Anhand eine Paneldatensatzes untersucht dieses Papier den Zusammenhang zwischen Stahlnachfrage und BIP und dessen Komponenten, insbesondere dem Anteil der Investitionen am BIP, da Investitionsgüter erwartungsgemäß besonders stahlintensiv sind. Die Analyse bestätigt, dass es im Zuge der wirtschaftlichen Entwicklung zunächst einen Anstieg der Stahlnachfrage zu geben scheint, dem ein tendenzieller Rückgang folgt, nachdem Volkswirtschaften ein bestimmtes Pro-Kopf-Einkommen erreicht haben. Zudem finden wir Hinweise dafür, dass 'carbon leakage' scheinbar keine Rolle im Stahlsektor spielt.
Keywords: L61; C33; Q53; 330; Steel consumption; intensity of use-hypothesis; carbon leakage